Dharmawang a's heritage On the appreciation of the Old Javanese Mah bh rata - van der Molen, Willem (Wacana, Journal of the Humanities of Indonesia, 2010)
As we all know, the Old Javanese Mah bh rata was not created from scratch by a Javanese author but was translated (in some sense) from the Sanskrit. The story of Hi imb reveals an interesting difference between the Old Javanese version and the Sanskrit version of the text. In the latter2 Hi imb appeals to Kunt , Bh ma's mother, after Bh ma keeps rejecting her. However, it is not Kunt who gives the answer but Yudhi hira, her son: he is the one who gives permission to Hi imb to take Bh ma as her husband. We should remember that Kunt at this point in the story is a widow; her husband died a long time ago. Yudhi hira is her eldest son. In the Old Javanese version it is Kunt herself who answers Hi imb . This difference between the Sanskrit Mah bh rata and the Old Javanese Mah bh rata is interesting, because it reflects a well-known difference between traditional Indian and Indonesian societies concerning the position of women. It is archetypical for the difference between the two versions of the text in general: the Old Javanese version follows the story faithfully but gives its own twist to it. This interpretation, I have to admit, is not generally accepted. The established scholarly opinion has it that the Old Javanese Mah bh rata is a shortened derivative, meaning that it copies or imitates the Sanskrit story, shortening it without adding anything new to the story.